The Principles of Marketing Management in Social Organizations - Mruk, Henryk (Studia Oeconomica Posnaniensia, 2015)
Effective management of social organizations requires the application of the concept of marketing. The aim of the article is a critical presentation of the principles of marketing management in social organizations. It discusses the concepts of building and implementing a marketing strategy. It describes how to build a market position and promote the organization’s environment. The importance of personnel qualification for the achievement of the objectives of social organization are also highlighted.